(untitled) (Research, Society and Development, 2021)
Asperger Syndrome (AS) is a neurodevelopmental disorder that progresses with significant deterioration in the individual’s social, occupational and other important activities. People with the syndrome usually have memorization skills and are good at math or science. AS is a recent disease, where there is still controversy about diagnosis and treatment, tending to be underdiagnosed. Objective: To evaluate the presence of clinical aspects of AS among students, technicians and professors at a federal university in the interior of Minas Gerais, Brazil. Methodology: The Australian Scale for AS was applied through an online questionnaire and the score data were analyzed by the ANOVA test and the Pearson correlation test, using the GraphPrism 5.0 statistical program, considering a significance level of p<0.05. Results: The study showed a low incidence of clinical aspects of AS among the institution’s professors, students and technicians, with higher scale scores being found among students and professors in the sciences and humanities, and the smallest in the field. of health. Conclusion: The population studied showed few clinical aspects for AS since the lowest scores were more prevalent among individuals.